2019
DOI: 10.15294/biosaintifika.v11i1.16532
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Potential Use of Macro Algae in Pesisir Barat Lampung

Abstract: Pesisir Barat Regency in Lampung has abundant marine biological wealth that has not been widely known and utilized by the community, one of them is macro algae. The objectives of the research were to identify the types of macro algae and to explains the potential use of macro algae in the Pesisir Barat Lampung Region. The study used cruise method. The findings were identified by experts to validate the results of classification, morphology, and qualitative studies regarding the potential use and benefits of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Kusumawati et al (2022) and Zainol et al (2019) mentioned that using HCl in calcium extraction will dissolve the calcium and the organic compounds, such as protein. The existing correlation between the extraction method and using HCl to extract will benefit the calcium food enrichment (Asih et al 2019). Rosnah et al (2021) reported that 4% HCl could be used for calcium extraction in chicken egg cells.…”
Section: Introductionmentioning
confidence: 99%
“…Kusumawati et al (2022) and Zainol et al (2019) mentioned that using HCl in calcium extraction will dissolve the calcium and the organic compounds, such as protein. The existing correlation between the extraction method and using HCl to extract will benefit the calcium food enrichment (Asih et al 2019). Rosnah et al (2021) reported that 4% HCl could be used for calcium extraction in chicken egg cells.…”
Section: Introductionmentioning
confidence: 99%
“…Agar, having the ability to form a gel, can be used as an emulsi er, stabilizer, gelling agent, or thickener. This product is usually extracted from seaweed using the hot water extraction method in acidic conditions (Asih et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…serves as an excellent source of polysaccharide, i.e. agar also rich in pigmented antioxidants such as chlorophyll and carotenoids (Stengel et al, 2015;Asih et al, 2019). Polysaccharides from seaweed are frequently related to pharmacological activities (Hamed et al, 2015) such as anticoagulant, antioxidant (Yudiati et al, 2018a;2018b), antitumor, and immunomodulatory of shrimp (Litopenaeus vannamei) (Yudiati et al, 2016(Yudiati et al, , 2019 as well as Zebrafish (Yudiati et al, 2020) Common salinity at sea in marine waters is around 35 ppt.…”
Section: Introductionmentioning
confidence: 99%